Efficient Hydrogen Evolution via 1T‐MoS2/Chlorophyll‐a Heterostructure: Way Toward Metal Free Green Catalyst. Issue 4 (19th February 2023) - Das, Debmallya; Manna, Jhimli; Bhattacharyya, Tarun Kanti
Abstract: Electrocatalytic hydrogen evolution reaction (HER) is regarded as a sustainable and green way for H2 generation, which faces a great challenge in designing highly active, stable electrocatalysts to replace the state‐of‐art noble metal‐platinum catalysts. 1T MoS2 is highly promising in this regard, but the synthesis and stability of this is a particularly pressing task. Here, a phase engineering strategy has been proposed to achieve a stable, high‐percentage (88%) 1T MoS2 /chlorophyll‐a hetero‐nanostructure, through a photo‐induced donation of anti‐bonding electrons from chlorophyll‐a (CHL‐a) highest occupied molecular orbital to 2H MoS2 lowest unoccupied molecular orbital. The resultant catalyst has abundant binding sites provided by the coordination of magnesium atom in the CHL‐a macro‐cycle, featuring higher binding strength and low Gibbs‐free energy. This metal‐free heterostructure exhibits excellent stability via band renormalization of Mo 4d orbital which creates the pseudogap‐like structure by lifting the degeneracy of projected density of state with 4S in 1T MoS2 . It shows extremely low overpotential, toward the acidic HER (68 mV at the current density of 10 mA cm −2 ), very close to the Pt/C catalyst (53 mV). The high electrochemical‐surface‐area and electrochemical turnover frequency support enhanced active sites along with near zero Gibbs free energy. Such a surface‐reconstruction strategy provides a new avenue toward the production of efficient non‐noble‐metal‐catalysts for the HER with the aim of green‐hydrogen production. Abstract : The study proposes metal‐free‐electrocatalytic hydrogen evolution by a stable 1T‐MoS2‐chlorophyll‐a heterostructure synthesized by a unique photoinduced‐phase‐engineering strategy, this can lift up the technological barriers of the dimensional engineering and interfacial‐instability which seriously hinder the scalable production of metallic (1T) transition metal dichalcogenides monolayers and can help in commercial releasing.